Diagnosability of interconnection networks: past, present and future. Issue 1 (2nd January 2020) - Cheng, Eddie; Qiu, Ke; Shen, Zhizhang
ABSTRACT: Diagnosability is an important topic in analyzing vulnerability and resilience issues of interconnection networks. In this short commentary, we outline the development of this topic.